Multi-component filters for domestic graywater treatment in village houses - Radin Mohamed, Radin Maya Saphira (American Water Works Association, 2016)
The majority of village houses in Malaysia generate graywater— from kitchens, bathrooms, sinks, and laundry—that is discharged directly into rivers or main drains without any treatment. These practices have a critical impact on humans and the environment. Therefore, this pilot-scale study aimed to design a natural filtration system that consists of clamshells, steel slag, limestone, and sand media for treatment of graywater. The filtration system was designed with 24 L of capacity and fixed at the discharge point of graywater in village houses. The filtration system exhibited high efficiency for treatment of household graywater, with 87.7% of removal for biochemical oxygen demand, 74.0% for chemical oxygen demand, 96.2% for total suspended solids, and 98% for turbidity with a pH of 7.87. The filtrated graywater met the limits required by Malaysia’s 1974 Environmental Quality Act, 2009 regulations, Standard A, for disposal upstream of drains.